HUBUNGAN ANTARA KETERAMPILAN KOMUNIKASI DENGAN SELF CONFIDENCE SISWA SMK - Rahman, Rizal; Mustakim, Mustakim; Anam, M. Chairul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study was motivated by the importance of communication skills in developing students’ self-confidence within the school environment. Poor interpersonal communication skills may affect students’ courage to express opinions, engage in social interactions, and demonstrate their potential optimally. The purpose of this study was to determine the relationship between communication skills and self-confidence among eleventh-grade students at SMKN 1 Batulayar in the 2019/2020 academic year. This study employed a quantitative approach with a correlational research design. The population consisted of 80 students, and all members of the population were used as research subjects. Data were collected using questionnaires as the primary method, while observation, interviews, and documentation were used as supporting methods. Data analysis was conducted using the Product Moment correlation technique. The findings revealed a significant positive relationship between communication skills and students’ self-confidence. These findings indicate that better communication skills are associated with higher levels of self-confidence in social interaction and adaptation within the school environment. This study implies that improving communication skills can be an important strategy in enhancing students’ self-confidence through guidance and counseling services at school. Penelitian ini dilatarbelakangi oleh pentingnya keterampilan komunikasi dalam membangun kepercayaan diri siswa pada lingkungan sekolah. Kurangnya kemampuan komunikasi interpersonal dapat memengaruhi keberanian siswa dalam menyampaikan pendapat, berinteraksi sosial, dan menampilkan potensi diri secara optimal. Penelitian ini bertujuan untuk mengetahui hubungan antara keterampilan komunikasi dengan kepercayaan diri (self confidence) siswa kelas XI di SMKN 1 Batulayar Tahun Pelajaran 2019/2020. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian berjumlah 80 siswa dan seluruh populasi dijadikan subjek penelitian. Teknik pengumpulan data menggunakan angket sebagai metode utama, sedangkan observasi, wawancara, dan dokumentasi digunakan sebagai metode pelengkap. Analisis data dilakukan menggunakan korelasi Product Moment. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara keterampilan komunikasi dan self confidence siswa. Temuan ini mengindikasikan bahwa semakin baik keterampilan komunikasi siswa, maka semakin tinggi pula tingkat kepercayaan dirinya dalam berinteraksi dan menyesuaikan diri di lingkungan sekolah. Penelitian ini memberikan implikasi bahwa pengembangan keterampilan komunikasi dapat menjadi salah satu upaya penting dalam meningkatkan kepercayaan diri siswa melalui layanan bimbingan dan konseling di sekolah.